Student Perceptions of Secondary Education Teaching Effectiveness: General Profile, the Role of Personal Factors, and Educational Level - Fernández-García, Carmen-María; Maulana, Ridwan; Inda-Caro, Mercedes; Helms-Lorenz, Michelle; García-Pérez, Omar (Frontiers in Psychology, 2019)
The purpose of this study was to examine student perceptions of teaching behavior. Additionally the aim was to examine if teacher characteristics (educational level, gender, and teaching experience) could explain differences in student perceptions of their teachers. Teaching behavior was studied from the research on teaching and teacher effectiveness perspective. Secondary students (N = 7,114), taught by 410 teachers in Spain, participated in the study. Survey data were analyzed using non-parametric tests, Kruskal-Wallis, U Mann-Whitney with Bonferroni correction, and the analysis of effect sizes. Furthermore, a regression model was applied. Results showed that teaching behavior was perceived as sufficient to good, depending on the teaching behavior domain. Results indicated interesting differences between lower secondary education, upper secondary education and vocational education and training teachers. The effect size values (rU statistic) ranged between 0.43 and 0.63, highlighting the significant effect of teachers’ teaching experience on the six teaching skills domains: learning climate, efficient classroom management, clarity of instruction, activating teaching, differentiation, and teaching learning strategies. Those teachers with less teaching experience were the ones who showed higher scores. Findings from the regression model showed that educational level had a significant predictive effect on the six teaching skills domains, mainly for male teachers. However, in several domains female teachers were perceived by students to outperform their male counterparts.